Coastal erosion and environmental change in the Cabanes-Torreblanca wetland (Castelló). Data for sustainable management - P. Carmona González J. M. Ruiz Pérez y M. Ibáñez Solaz (Boletín de la Asociación de Geógrafos Españoles, 2014)
Resumen